Surface chemistry of graphene tailoring the activity of digestive enzymes by modulating interfacial molecular interactions - Tang, Huan; Yang, Tong; Chen, Lin; Zhang, Ying; Zhu, Yinhua; Wang, Chen; Liu, Dandan; Guo, Qiuyan; Cheng, Guangqing; Xia, Fei; Zhong, Tianyu; Wang, Jigang (Journal of colloid and interface science, 2023)
[Display omitted] As a kind of novel functional material, graphene-related nanomaterials (GRMs) have great potentials in industrial and biomedical applications. Meanwhile, the production and wide application of GRMs will increase the risk of unintended or intentional oral exposure to human beings, attracting safety concerns about their biological fates and toxicological effects. The normal enzymatic activity of digestive enzymes is essential for the proper functioning of the gastrointestinal tract system. However, whether and how orally entered GRMs and their surface groups affect digestive enzymes’ activity are still scarce. In this paper, we systematically studied the effects of graphene oxide (GO), graphene modified with hydroxyl groups (OH-G), carboxyl groups (COOH-G), and amino groups (NH2-G) on enzymatic activity of three typical digestive enzymes (pepsin, trypsin, and α-pancreatic amylase). The results showed that the activity of trypsin and α-pancreatic amylase could be greatly changed after GRMs incubation in a surface chemistry dependent manner, while the activity of pepsin was not affected. To elucidate the mechanisms at the molecular level, the interactions between trypsin and GRMs were studied by spectrometry, thermophoresis, and computational simulation approaches, and the key roles of surface chemistry of GRMs in tailoring the activity of trypsin were finally figured out. GO allosterically inhibited trypsin’s activity in the non-competitive manner because of the conformation transition induced by the intensive interactions. COOH-G could effectively hamper enzymatic activity of trypsin in the competitive manner by blocking the active catalytic pocket. As for NH2-G and OH-G, they had little impact on the activity of trypsin due to the weak binding affinity or limited conformational change. Our findings not only indicate surface chemistry plays an important role in tailoring the effects of GRMs on the activity of digestive enzymes but also provide new insights for understanding the oral safety of nanomaterials from daily products and the environment.